2020
DOI: 10.2139/ssrn.3580302
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Unequal Social Distancing across Demographic Groups

Abstract: This paper analyzes whether social distancing experienced by alternative demographic groups within the U.S. has been di¤erent amid COVID-19. The formal investigation is achieved by using daily state-level mobility data from the U.S. covering information on the demographic categories of income, education and race/ethnicity.The results show that social distancing has been experienced more by higher-income, higher-educated or Asian people after the declaration of National Emergency on March 13th, 2020. Since alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
4
1
1
Order By: Relevance
“…Both resonates with a sense of elitism and self-interest that has been anecdotally evident in high profile cases of individuals in the UK who have intentionally broken SD rules. Overall, the finding on higher degree qualification contrasts with the large body of research that associates greater educational attainment with adherence [ 16 , 22 ], although of note is an exception from a UK study about the Swine Flu pandemic [ 20 ]. Whilst political preference is in line with a study that found British people with more progressive beliefs as observing more SD behaviour [ 31 ], another study on political preference provided no association to compliance [ 59 ].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Both resonates with a sense of elitism and self-interest that has been anecdotally evident in high profile cases of individuals in the UK who have intentionally broken SD rules. Overall, the finding on higher degree qualification contrasts with the large body of research that associates greater educational attainment with adherence [ 16 , 22 ], although of note is an exception from a UK study about the Swine Flu pandemic [ 20 ]. Whilst political preference is in line with a study that found British people with more progressive beliefs as observing more SD behaviour [ 31 ], another study on political preference provided no association to compliance [ 59 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Black, Asian and Minority Ethnic (BAME) populations in the UK have been found to be at greater risk of dying from COVID-19 compared to the white population [ 18 ], and evidence suggest this is multi-factorial (material deprivation, increased exposure to risk and structural racism amongst others [ 19 ], yet findings from previous pandemics and COVID-19 suggest that this is not due to poorer adherence to SD measures [ 20 , 21 ]. Higher socio-economic status and higher educational attainment are often related to engagement in SD behaviours [ 14 16 , 22 ], although both low income and having no qualifications have also been associated with greater adherence to SD behaviours in a UK study [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Black, Asian and Minority Ethnic (BAME) populations in the UK have been found to be at greater risk of dying from COVID-19 compared to the white population (14), and evidence suggest this is multi-factorial (material deprivation, increased exposure to risk and structural racism amongst others (15), yet ndings from previous pandemics and COVID-19 suggest that this is not due to poorer adherence to SD measures (16,17). Higher socio-economic status and higher educational attainment are often related to engagement in SD behaviours (10)(11)(12)18), although both low income and having no quali cations have also been associated with greater adherence to SD behaviours in a UK study (16).…”
Section: And the Independent Sagementioning
confidence: 99%
“…Aliado a isto, o racismo também condiciona a adoção de medidas preventivas para Covid-19, considerando que o distanciamento social, a principal medida elencada pela Organização Mundial de Saúde (WHO, 2020), não é um privilégio de todos, em especial no Brasil, onde negras e negros representam a maioria dos trabalhadores informais, de serviço doméstico, comercial, da alimentação, transporte, armazenamento e correio, que se mantiveram ativos, mesmo durante a pandemia. Estudo realizado nos EUA mostra que a adoção do distanciamento social é maior entre brancos, ricos e com maior escolaridade, quando comparada à população negra (Yilmazkuday, 2020). A higienização das mãos, outra medida preventiva para Covid-19 recomendada pela WHO (2020), é muitas vezes difícil de executar, visto que, muitas moradias, em diversas regiões do país, não têm acesso a água e saneamento básico, como mencionado anteriormente .…”
Section: Introductionunclassified